SCREENING INDIGENOUS RHIZOSPHERIC ACTINOMYCETES AS BIOCONTROL AGENT TOWARD WHITE ROOT FUNGUS IN NUTMEG PLANTS IN SOUTH ACEH - Agustinur, Agustinur; Maulidia, Vina; Chairudin, Chairudin; Subandar, Irvandar (Jurnal Agrotek Tropika, 2025)
White root disease, caused by the Rigidoporus fungal group, is a serious threat to nutmeg (Myristica fragrans) production, with yield losses reaching up to 70%. The fungus infects through the rhizosphere, making root systems particularly vulnerable. While inorganic pesticides have been widely used to manage this disease and minimize yield loss, their long-term use poses serious environmental and health risks due to toxicity and persistence. Therefore, the development of environmentally friendly alternatives, such as biological control agents, is urgently needed. Actinomycetes, a group of soil-dwelling microorganisms known for their ability to produce antifungal secondary metabolites, represent a promising biocontrol resource. This study aimed to isolate and screen indigenous actinomycete isolates with antagonistic potential against white root fungus. Soil samples were collected from the rhizosphere of nutmeg plants in South Aceh. Actinomycetes were isolated and purified on selective agar media, followed by dual culture bioassays to assess their antifungal activity. A total of 22 actinomycete isolates were obtained, with 17 exhibiting antagonistic effects against white root fungus. Four isolates STJ 10, STJ 06, STS 07, and STS 26 demonstrated strong inhibitory activity, with inhibition zones of 31.84 mm, 21.68 mm, 21.36 mm, and 21.97 mm, respectively. The results highlight the potential of indigenous actinomycetes as effective and sustainable biocontrol agents for managing white root disease in nutmeg. This contributes to the advancement of eco-friendly plant protection strategies and supports long-term agricultural sustainability in tropical cropping systems.